Under-Ice Light Field in the Western Arctic Ocean During Late Summer - Veyssière, Gaëlle; Castellani, Giulia; Wilkinson, Jeremy; Karcher, Michael; Hayward, Alexander; Stroeve, Julienne C.; Nicolaus, Marcel; Kim, Joo-Hong; Yang, Eun-Jin; Valcic, Lovro; Kauker, Frank; Khan, Alia L.; et al. (Frontiers in Earth Science, 2022)
The Arctic is no longer a region dominated by thick multi-year ice (MYI), but by thinner, more dynamic, first-year-ice (FYI). This shift towards a seasonal ice cover has consequences for the un-der-ice light field, as sea-ice and its snow cover are a major factor influencing radiative transfer and thus, biological activity within- and under the ice. This work describes in situ measurements of light transmission through different types of sea-ice (MYI and FYI) performed during two expedi-tions to the Chukchi sea in August 2018 and 2019, as well as a simple characterisation of the bio-logical state of the ice microbial system. Our analysis shows that, in late summer, two different states of FYI exist in this region: (i) FYI in an enhanced state of decay, and (ii) robust FYI, more likely to survive the melt season. The two FYI types have different average ice thicknesses: 0.74+0.07 m (N=9) and 0.93+0.11 m (N=9), different average values of transmittance: 0.15+0.04 compared to 0.09+0.02, and different ice extinction coefficients: 1.49+0.28 and 1.12+0.19 m-1. The measurements performed over MYI present different characteristics with a higher average ice thickness of 1.56+0.12 m, lower transmittance (0.05+0.01) with ice extinction coefficients of 1.24+0.26 m-1 (N=12). All ice types show consistently low salinity, chlorophyll a concentrations and nutrients, which may be linked to the timing of the measurements and the flushing of melt-water through the ice. With continued Arctic warming, the summer ice will continue to retreat, and the decayed variant of FYI, with a higher scattering of light, but a reduced thickness, leading to an overall higher light transmittance, may become a more relevant ice type. Our results suggest that in this scenario, more light would reach the ice interior and the upper-ocean.